Disaster mechanism and dynamic manifestation control of rock burst in the Ordos Mining Area - Zhen WU; Heng GAO; Zhaofeng FAN; Tianliang HU; Xiaohu WANG; Xuegang WANG; Jinpeng YAO (Meikuang Anquan, 2025)
The layout of coal mining in our country is gradually being optimized towards the western regions, the mining depth is constantly extending deeper, and the hazards of rock burst are becoming increasingly severe. To achieve effective prevention and control of rock bursts in Ordos Mining Area, the primary task is to clarify the main controlling factors causing these rock bursts. Based on the investigation of 28 coal mines in Ordos Mining Area with burial depth of over 400 meters, four geological controlling factors causing rock bursts have been summarized: mining depth, coal seam thickness, coal-rock burst tendency, and roof rock structure, along with two engineering controlling factors: coal pillar design and extraction speed. The mechanical mechanisms of each main controlling factor influencing the occurrence of rock burst were analyzed. In terms of the main geological control factors, the increase in mining depth leads to an increase in coal and rock stress, and the thickness of coal seams shows a positive correlation with the possibility of rock burst. The burst tendency of coal and rock is an inherent factor measuring the ability of coal and rock to accumulate and release energy during burst events. A hard and thick suspended roof structure can lead to increased pre-stress concentration, and when the roof breaks, it releases a large amount of kinetic energy, forming dynamic loads that act on the surrounding rock of tunnels, inducing rock bursts. In terms of the main control factors of the project, unreasonable width of coal pillars leads to stress concentration and energy accumulation which are significant factors causing rock bursts in retreating tunnels. Excessive extraction speed increases the length of suspended roofs and the degree of stress concentration, resulting in more kinetic energy being released when the roof breaks. Based on these findings, a comparative analysis of dynamic events during the mining operations of Hongqinghe Coal Mine, Menkeqing Coal Mine, Nalinhe Coal Mine, and Shilawusu Coal Mine was conducted. Recommendations for coordinated regional and local prevention and control strategies for rock bursts are proposed.